2021
DOI: 10.1101/2021.04.20.21255794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccination acceptance among healthcare workers in Germany

Abstract: BackgroundVaccination hesitancy is a serious threat to achieve herd immunity in a global and rapidly changing pandemic situation. Health care workers play a key role in the treatment of patients with Coronavirus disease 2019 (COVID-19) and in promoting vaccination in the general population. The aim of the study was to provide data on COVID-19 vaccination acceptance and barriers among healthcare workers in Germany to support health policymakers choosing specific vaccination campaign strategies.MethodsAn online … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Studies conducted globally on COVID-19 vaccine acceptance among HCPs have reported wide variations in vaccine hesitancy ranging from 8.3% to 72.4%. 4,8,14,15,[30][31][32][33][34][35][36][37][38][39] Notably, some studies were conducted before vaccines were approved and/or rolled out, 15 and HCPs in some studies had already received vaccines. 32 Our study was conducted at the start of the national vaccine campaign in Barbados began in February 2021.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies conducted globally on COVID-19 vaccine acceptance among HCPs have reported wide variations in vaccine hesitancy ranging from 8.3% to 72.4%. 4,8,14,15,[30][31][32][33][34][35][36][37][38][39] Notably, some studies were conducted before vaccines were approved and/or rolled out, 15 and HCPs in some studies had already received vaccines. 32 Our study was conducted at the start of the national vaccine campaign in Barbados began in February 2021.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,14,15,[30][31][32][33][34][35][36][37][38][39] Notably, some studies were conducted before vaccines were approved and/or rolled out, 15 and HCPs in some studies had already received vaccines. 32 Our study was conducted at the start of the national vaccine campaign in Barbados began in February 2021. The vaccine hesitancy we report is consistent with some studies conducted…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, most previous studies carried out globally were conducted in periods when COVID-19 vaccines were not available or accessible only to certain groups, such as healthcare workers or key workers. 43,44 It is also of outright importance to investigate the factors influencing perception of COVID-19 vaccination at the local level, as vaccination hesitancy may be widely influenced by regional and cultural factors.…”
Section: Discussionmentioning
confidence: 99%